2014
DOI: 10.1097/sap.0b013e318284084b
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Early Flap Coverage in Deep Sternal Wounds

Abstract: This study suggests that chronic infection after flap reconstruction in DSWI is associated with late flap cover. We suggest the need for a consensus agreement on the combined care and early management of DSWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…[19][20][21] These results indicate that early identification of patients who would benefit from a flap reconstruction could provide the patients with a shorter hospital stay and quicker recovery. In line with this observation, Lo et al 15) found that each day of delay for flap coverage significantly increased the risk of chronic infection. Furthermore, Cabbabe et al 16) found patients undergoing one step radical debridement with muscle flap coverage had significantly shorter hospital stay and lower mortality compared to patients with DSWI who were referred to flap coverage after undergoing extended management by the thoracic surgeons.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…[19][20][21] These results indicate that early identification of patients who would benefit from a flap reconstruction could provide the patients with a shorter hospital stay and quicker recovery. In line with this observation, Lo et al 15) found that each day of delay for flap coverage significantly increased the risk of chronic infection. Furthermore, Cabbabe et al 16) found patients undergoing one step radical debridement with muscle flap coverage had significantly shorter hospital stay and lower mortality compared to patients with DSWI who were referred to flap coverage after undergoing extended management by the thoracic surgeons.…”
Section: Discussionmentioning
confidence: 48%
“…Little evidence exists in the literature regarding the specific timing of flap reconstruction after DSWI. 15) Although some authors have proposed immediate debridement and flap coverage as the superior procedure, 5,16) others advocate TNP therapy and rewiring. 17) Although TNP therapy has the big advantage of allowing the medical staff relatively easy access to evaluate the healing progress of the DSWI defect, a subset of patients will not heal in time using TNP therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…The second factor to impact outcome is the timing between recognition of a deep sternal infection and surgical intervention. 16 , 19 , 22 24 Lo et al 25 calculated that each day of delay from diagnosis to flap coverage increased the risk of chronic wound infection by a factor of 1.2/day. The third factor is the adequacy of debridement of all infected tissue and contaminated foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, the treatment of sternal wound infections has evolved considerably leading to major improvements in both survival and morbidity [10]. There is, however, no consensus relating to the most suitable treatment strategy, timing and reconstructive technique [3,10,11]. Multiple treatment algorithms have been proposed in an attempt to standardize the management of this morbid complication but none has achieved widespread general acceptance [4,5,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The advancement flaps may not reach sufficiently to cover the defects in the most caudal third of the sternum. A direct closure of the skin is often attempted, although sometimes this can lead to unwanted tension and wound-healing problems[10,11,13]. With large defects, skin grafts have to be used leading to suboptimal cosmetic results[3,8].The rectus abdominis muscle flap may be used if the pectoralis major muscle flap is unavailable or when it has an insufficient reach to the most caudal third of the sternum.…”
mentioning
confidence: 99%